Uniform Resource Locator (URL) Detection Security System Based on Android - Haruno Sajati; Harliyus Agustian; Eko Murdiansyah (Compiler, 2019)
The use of the internet, which is currently increasing dramatically, certainly brings the convenience of finding information. The increase in internet usage also eventually gave rise to cybercrime crimes, one of which was by spreading a URL or fake site to steal someone's personal data. The research done is how to build an Android-based application that can detect the security of a URL. The goal is that internet users, especially social media, can avoid cybercrime crime that wants to steal personal data. Making an application uses the Regular Expression method to analyze each line of the Webpage Source Code in the URL based on 8 criteria taken from the World Wide Web Consortium (W3C). The application was then tested with 10 phishing-charged URLs and compared with Kaspersky, McAfee, and AdBlock applications. Based on the results of trials and comparisons, applications that have been made are able to detect 6 or 60% of the 10 URLs. Kaspersky and McAfee applications can detect 70%, while AdBlock only detects 3 or 30% of 10 URLs that contain phishing.